2017
DOI: 10.1016/j.rboe.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pelvic ring fractures and injuries

Abstract: ObjectiveThis study evaluated the pelvic ring fractures and injuries in patients admitted to and treated at this ward between August, 2012 and January, 2014.Methods66 patients were submitted to treatment protocols according to their age, gender, skin color, injury mechanism, location of the trauma, classification of their injuries, emergency intervention, associated injuries, injured side of the body, treatment, and mortality. The most relevant data were classified according to statistic procedures, such as Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
4
35
4
3
Order By: Relevance
“…Tile A classification of pelvic fracture is the most common type of pelvic fracture in the present cohort, which is similar to some of the studies that reported stable fractures as the most frequent fracture type [40]. On the other hand, an earlier study from the Netherlands reported Tile B fractures to be predominantly followed by Tile C and Tile A fractures [41].…”
Section: Discussionsupporting
confidence: 90%
“…Tile A classification of pelvic fracture is the most common type of pelvic fracture in the present cohort, which is similar to some of the studies that reported stable fractures as the most frequent fracture type [40]. On the other hand, an earlier study from the Netherlands reported Tile B fractures to be predominantly followed by Tile C and Tile A fractures [41].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with our finding, Keykhosro Mardanpour, et al, [9] and Gilberto José, et al, [10] stated that males were affected more than females and road traffic accidents were the most common cause of pelvic fractures, followed by fall from a height.…”
Section: Discussionsupporting
confidence: 92%
“…Tile A classification of pelvic fracture was the commonest type of pelvic fracture in the present cohort which is similar to some of the studies that reported stable fractures as the most frequent fracture type [30]. On the other hand, an earlier study from the Netherlands reported Tile B fractures to be predominantly followed by Tile C and Tile A fractures [31].…”
Section: Discussionsupporting
confidence: 89%